Electromyographic fatigue evaluation of back and hip extensor muscles and its relationship with anthropometric characteristic of athletes with chronic low back pain - Khorsandi Kolur, M.; Norasteh, A. A.; Daneshmandi, H. (Medicina dello Sport, 2011)
Aim. The aim of the study was to measure back and hip extensor muscle fatigue during Sorensen back endurance test in chronic low back pain (CLBP) athletes and healthy controls, and investigation of relationship between the back and hip extensor muscle fatigability and subject›s anthropometric characteristics.